Kumar & Clark's clinical medicine - Kumar, Parveen J. (Parveen June); Clark, Michael L. (Saunders Elsevier, 2012)
'This book is comprehensive, student friendly (if still intimidating in size!) and covers such a vast breadth of knowledge. It still remains the primary 'must-have' text book of any budding doctor, or qualified one at that. This book is stunning in its breadth and in its ease of use. It still remains as the 'gold-standard' thorough guide to clinical medicine its forefathers were.